Monitoring of Determination Features of Gastronomic Events Efficiency - Mykola Ohiienko (Ресторанний і готельний консалтинг: Інновації, 2020)
Topicality. Today, gastronomic tourism in theBlack Sea region is under development. a large number of scientists are engaged in the gastronomic culinary development activities and the study of their economic efficiency and promotion in Internet communications, but its impact on the quality of events is insufficiently studied. Therefore, conducting analytical research on the announcement and post-event publications in the information Internet resources of gastronomic events becomes an urgent task.